Establishing Rapport with the Reader: Engagement Markers in the Discussion Section of a Research Article - Elena V. Tikhonova; Marina A. Kosycheva; Tatiana Yu. Golechkova (National Research Mordova State University, 2023)
Introduction. The paper studies the use of engagement markers in discussion sections of English-medium research articles in medical and foreign language teaching domains by two groups of academic writers, Anglophone and non-native ones using English as a Lingua Franca. Materials and Methods. In order to explore how disciplinary considerations and author language backgrounds affect the choice, frequency and distribution of engagement markers, we built a corpus of 68 research papers (34 medical and 34 EFL papers) published in international and national academic journals between 2019 and 2022. The markers were investigated using contrastive analysis applying Hyland & Jiang's modified model. Results. Corpus analysis stressed both cross-disciplinary and language distinctions. The analysed foreign language teaching research papers rely on engagement more than the medical papers, which is manifested in the frequency of the use of markers. Writers in both disciplines engage with the reader through reader mentions and appeals to shared knowledge, but unlike medical papers, teaching ones rely heavily on managing the readers' attention and addressing them directly through asides. From the linguacultural perspective, Anglophone writers use engagement markers a little more frequently than the authors from non-English-speaking countries. The main distinction lies in direct addresses to the reader which are realised in personal asides and questions. Overall, Anglophone writers tend to use a broader variety of engagement markers than non-Anglophone authors. The frequency and selection of engagement markers are influenced by language background, reflecting differences in linguistic-cultural conventions, target audiences, and publication contexts. Within the global scientific community, it is crucial to investigate how multilingual authors navigate the use of metadiscourse markers. Native English speakers and non-native speakers engage in a dialogue as equals, disregarding linguistic dominance. This highlights the need for unified conventions in establishing a global academic lingua franca. Discussion and Conclusion. The findings of this study hold significant pedagogical implications, providing support for academic writers and promoting the development of a global academic language and culture. By understanding the dynamics of engagement markers and their role in effective communication, pedagogical efforts can focus on enhancing global academic language skills and fostering a cohesive global academic culture.